BS EN 2266-008. Aerospace series. Cables, electrical, for general purpose. Operating temperatures between -55 °C and 200 °C. Part 008. DRP (pair) DRT (3 cores) DRQ (4 cores) family, multicore UV laser printable jacketed cable. Product standard (19th November 2019) - British Standards Institution,
No abstract available